THE ANALYSIS OF POSSIBILITY OF APPLICATION IN UKRAINE OF THE ROLLING STOCK WITH TILTING BODY CARS WHEN ORGANIZING HIGH-SPEED TRAFFIC - Zubko, A. P.; Korzhenevych, I. P.; Kurhan, M. B.; Kurhan, D. M. (Science and Transport Progress, 2004)
The authors have carried out an analysis and established the sphere of application of rolling stock with forced inclination of the car bodies.